Paraphrase the Obstacles to the Recycling of Construction and Demolition Waste: A Perspective of the Evolutionary Game of Three Stakeholders - Zhangli Chen; Keying Li; Haowen Tan; Jiawen Liu; Xizhen Wu; Peng Wang (Buildings)
With China’s urbanization, the construction industry has generated massive construction and demolition waste (C&DW), leading to severe environmental pollution and social problems. However, the currently proposed policies have not promoted the sustainable development of the C&DW recycling market. This paper constructs a tripartite evolutionary game model of construction production enterprises, construction enterprises, and the government. The decision-making evolution laws of relevant stakeholders at different stages of the development of the C&DW recycling market are identified through equilibrium stability analysis. The results show that in the initial stage, the government can help encourage enterprises to participate in C&DW recycling through appropriate subsidy and penalty measures. As the recycling market matures, enterprises achieve profits through market mechanisms and the proportion of enterprises participating in recycling increases. At this time, the government no longer plays a leading role, and the strategy evolves into non-supervision. In addition, the government should design carbon emission reduction policies for carbon quota and trading according to the market status to exert positive effects. Hence, this study provides a theoretical basis for the governments of developing countries to effectively manage C&DW market development.